Image Encryption Techniques Using Dynamic Approach : An Article Review - Shuker, Dr. Wisam; Kubba, Zaid M. Jawad; Badrulddin, Ahmed; Mohammed Uliyan, Diaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this study, a chaotic method is proposed that generates S-boxes similar to AES S-boxes with the help of a private key belonging to In this study, dynamic encryption techniques are explored as an image cipher method to generate S-boxes similar to AES S-boxes with the help of a private key belonging to the user and enable images to be encrypted or decrypted using S-boxes. This study consists of two stages: the dynamic generation of the S-box method and the encryption-decryption method. S-boxes should have a non-linear structure, and for this reason, K/DSA (Knutt Durstenfeld Shuffle Algorithm), which is one of the pseudo-random techniques, is used to generate S-boxes dynamically. The biggest advantage of this approach is the production of the inverted S-box with the S-box. Compared to the methods in the literature, the need to store the S-box is eliminated. Also, the fabrication of the S-box has a very large key space as it depends on the user’s key. The encryption-decryption method allows changing pixel positions with the help of dynamically generated S-boxes, images, videos, etc. Thus, the study shows that a new method of S-boxes for dynamic cipher algorithms can be easily generated and applied to image encryption.